Techno‐economic assessment on the implementation of biomass gasifier in conventional parboiling rice mills. (16th December 2019) - Beno Wincy, W.; Edwin, M.
Summary: Enhancement of efficiency in rice processing mills can help rural farmers to reduce the cost of rice production. Parboiling‐the hydrothermal treatment of paddy rice, accounts for a significant portion of total rice processing costs and its quality. A rice husk powered gasifier‐based parboiling system is an attractive option for rural rice processing mills but has not been widely adopted due to various constraints. Hence, there is a need for technical and economical analysis on gasifier‐based rice parboiling system to generate information on efficiency improvement and the cost‐effective ways in rice processing industries. This paper presents a techno‐economic evaluation of rice husk powered gasifier‐based rice processing systems working in either Producer Gas in Hot Gas Mode (PG‐HGM) or Producer Gas in Cold Gas Mode (PG‐CGM). MATLAB software has been used for mathematical analysis. The research reveals that the biomass gasifier operated rice parboiling system working in both modes can have the overall system efficiency as 49% to 57% with a lowest payback time of 4‐2 years. Positive Net Present Cost is observed for the capacities above 1.5 tons/batch in PG‐HGM. Abstract : Process flow schemes of the proposed rice husk powered parboiling and drying system in Producer Gas in (a) Hot Gas Mode (PG‐HGM) and (b) Cold Gas Mode (PG‐CGM)